Binge watching the algorithmic catalog: an analysis of Twitter’s reaction to the launch of Netflix Italia - Giglietto, Fabio; Checcaglini, Chiara; Mazzoli, Lella (AoIR Selected Papers of Internet Research, 2016)
Following the end of September announcement, the on-demand streaming service Netflix was officially launched in Italy on October 22, 2015. The launch of Netflix allowed the Italian audience to experiment for the first time some of the exclusive features that made the service popular worldwide. On the one hand, Netflix made binge-watching easier by advancing to the next episode in the series and skipping unnecessary recaps. On the other hand, while also allowing to search and browse the catalog by genres, it default to a radically new metaphor of finding and discovering contents based on the algorithmic analysis of viewer’s preferences and tastes. While a constantly growing amount of literature is dedicated to both aspects, the launch of Netflix in the peculiar Italian market and the conversations it sparkled on social media, represent an extraordinary opportunity to study the ways viewers expected, reacted and made sense of those innovative features in the aftermath of the launch. Framed in the existing literature on binge-watching and algorithms, the study presents the results of a content analysis on Twitter’s conversations sparkled by the launch on Netflix Italia (N=17,623).